Os licenciandos em Física da UFS e as suas relações com o ensinar : uma investigação a partir da teoria da relação com o saber - Feitosa, Larissa Dias (2012)
This research is intended discover the relationship between the pre-service physics teacher and ―the teaching‖. The main questions that we try understand are: what the sense for teaching physics? What motivate the undergraduates in physics to teach physics? The theoretical basis adopted to make our analysis was the Theory of Relatioship with the knowledge, proposed by the French researcher Benard Charlot (2000, 2001, 2005 and 2009). We also looked for the purposes of theoretical analysis, the dialog between this author and others scholars that have researched about this theme, although this research has not been directed to the Education. Among them we highlight Lacan, Leontiev and Wallon. We also consider what Chevallard shows us, that is the importance of the institutional context to research about the relationship with knowledge or specific knowledge, which in our case is the teaching of physics. For this purpose, we try to explore features of the modern university and university education in physics, by authors such as Borges, Charlot et al, Chauí, Nóvoa, and some statistics data available about degree in physics in Brazil. It is a quantitative research, where an open questionnaire was used as a methodological tool, with a total of twenty questions. After applying the questionnaires to undergraduates in physics of São Cristóvão and Itabaiana campi of Federal University of Sergipe, a total of eighty-three questionnaires were retained for this analysis. With many arguments raised in the responses, we constructed a grid of categorization and through this we calculate the percentage of arguments most often cited by students. The main results suggest: the university as an institution charged with strong sense, in terms of obtaining knowledge for undergraduates; the choice of physics as academic careers rises with establishment of good relations with the physics education; the establishment of a positive relationship with the future practice of teaching prior to entering university, but without evidence of how this relationship is established; the job market as mediating factor between undergraduates and their choice of physics graduation; evidence that the choice of teaching in general, does not come from a "passion for teaching"; relations with teaching, permeated by the relationship with future students; belief in teaching high school physics and the teaching profession, despite the problems that comes with profession.